Beyond the Hype: Social Media Marketing and Purchase Intention in the Indian Cosmetic Industry - Peter, Liya; Mathew, John; George Mannaly Joseph , Christy (Tecno Scientifica Publishing, 2025)
This study explored the influence of Social Media Marketing (SMM) on the PI (PI) of female consumers of branded cosmetic products from the viewpoints of differential age and the possible mediating role of Consumer Scepticism (CS). A sample of 192 women in India was surveyed using a structured questionnaire, and the data were analysed using ANOVA, correlation, and mediation analysis with Hayes’ PROCESS Macro. The results indicated that younger consumers were more positive about SMM than older consumers, who were more sceptical. A significant positive relationship between SMM and PI was found, but CS did not mediate the relationship. The direct path between SMM and PI was significant (β = 0.5839, p < .001), while the indirect effects through CS were not. These findings demonstrated that SMM exerted a direct influence on purchase intentions and that marketers could gain more advantage from SMM by focusing on increasing authenticity and engagement rather than decreasing scepticism.